Sites of biosynthesis, distribution and phloem transport of 3-isobutyl-2-Methoxypyrazine in Capsicum annuum (bell pepper) plants - Zamolo, Francesca; Heinrichs, Jan Phillip; Wüst, Matthias (Phytochemistry (Oxford), 2023)
The distribution and translocation as well as the biosynthetic sites of 3-isobutyl-2-methoxypyrazine (IBMP) in bell pepper plants (Capsicum annuum) were examined. For IBMP-quantification, a stable-isotope dilution assay (SIDA) was developed, using headspace solid-phase microextraction (HS-SPME) combined with gas chromatography and time-of-flight mass spectrometry (ToF-MS). While IBMP was the most abundant MP in all aerial plant parts, IPMP was dominating in root tissues. The highest IBMP-levels were found in unripe bell pepper fruits. Moreover, feeding experiments with [2H10]-l-leucine revealed that IBMP is biosynthesized in all plant parts, while in roots and ripe bell pepper fruit tissues no incorporation of the labelled precursor was detectable. A potential phloem translocation of IBMP could not be detected. [Display omitted] •IBMP is detectable in the whole bell pepper plant.•Pericarp as the major site of IBMP accumulation.•No IBMP de novo biosynthesis in ripe fruit and root tissues.•IBMP could not be detected in the phloem.